Metformin and risk factors for chronic kidney disease in a European population based on Mendelian randomization - Xiaopei Liu; Xingyao Li; Peng An; Qi Gao; Yanhong Zhao; Xingmin Shi; Xili Wu (Renal Failure)
Background Metformin, widely used for type 2 diabetes, raises concerns about its use in chronic kidney disease (CKD) due to risks like lactic acidosis and renal function impact. This study uses Mendelian randomization (MR) and summary data-based MR (SMR) to explore metformin’s potential causal relationship with CKD and associated genes.Methods We employed MR methods (MR-Egger, weighted median, IVW) and sensitivity analyses to explore the causal relationship between metformin and CKD. SMR was used to analyze eQTL and CKD data from the UK Biobank and FinnGen, intersecting these with metformin drug targets to identify genes associated with CKD.Results MR analysis indicated that metformin may increase CKD risk (IVW model: OR = 144.67, p < 0.01). However, given the high OR value, additional studies are warranted to validate this finding. SMR identified genes ANPEP, STK11, ACACB, and RPS6KB as significantly associated with CKD risk.Conclusion The study suggests metformin could elevate CKD risk and identifies relevant genes. Clinicians should exercise caution when prescribing metformin, particularly for patients with renal issues. Further research is needed to confirm these findings and guide clinical practices.